Gestão da experiência do cliente: dimensões aplicadas ao contexto empresarial - Takahashi, Mayla Teixeira (2024)
This research aims to investigate the dimensions of customer experience management (CEM) in the Brazilian business context. For this purpose, qualitative research was conducted through interviews with 15 managers from different sectors. The results allow us to identify that CEM in the business context assumes a strategic role in the customer-centric vision. However, from policy to design and implementation of actions, or even measurement, there are a series of challenges faced by CE managers in B2B. This thesis has as a result the elaboration of a CEM model that supports alignment with corporate strategy, effectively capturing the voice of the customer, measuring the impact on the business in a solid and objective way so that a customer-centric culture can be developed, which are fundamental for success in an increasingly competitive market driven by consumer experience.